Covalent organic polymer derived N–doped carbon confined FeNi alloys as bifunctional oxygen electrocatalyst for rechargeable zinc-air battery. (29th April 2022) - Chen, Jun; Li, Liandong; Cheng, Yuanhui; Huang, Yan; Chen, Chang
Abstract: N–doped carbon confined FeNi alloys are promising candidate to noble Pt and IrO2 or RuO2 for oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) in rechargeable zinc-air batteries. However, it is difficult to control the distribution of transition metals in the precursor and electrocatalyst. Herein, we design a covalent organic polymer to realize the uniform distribution of metal, nitrogen and carbon precursors. The structure of the obtained electrocatalyst is FeNi nanoparticles coated with carbon shells dispersed on N-doped multilayer porous carbon (FeNi@NC). The resultant FeNi@NC delivered a half-wave potential for ORR of 0.878 V and a low potential of 1.59 V to achieve 10 mA cm −2 for OER, which surpasses commercial platinum/carbon and ruthenium dioxide. The outstanding bifunctional properties of FeNi@NC attribute to the synergistic coupling between N-doped carbon shells and dense FeNi nanoparticles. Moreover, the self-made zinc-air battery with FeNi@NC air-cathode displayed an excellent energy density of 137.7 mW cm − 2 as well as cycling stability (100 h, 200 cycles). Highlights: A novel N-rich covalent organic polymer was developed as a carbonaceous precursor for loading FeNi alloys. FeNi alloy nanoparticles are coated with several carbon layers. The FeNi@NC exhibits excellent ORR and OER catalytic activity in alkaline electrolyte. Zn-air battery with FeNi@NC catalyst exhibits high power density and long cycle life.